Evaluation of Changes in VO2max of FTME UPN Students in the First Two Semesters of Study: A Multistage Fitness Test Approach - Prijoto, Prijoto; Kurniati, Rizki; Yulianto, Wahyu Wibowo Eko; Indriharta, Lilik; Nugraheningsih, Ginanjar (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2025)
This study aims to evaluate changes in students' cardiorespiratory capacity at the Faculty of Mineral and Energy Engineering (FTME) UPN "Veteran" Yogyakarta during the first two semesters of the 2024/2025 academic year. Fitness measurements were conducted using the Multistage Fitness Test (MFT) on 154 male students at the beginning of semester 1 and the end of semester 2 to obtain VO2max estimates. During the two semesters, students took Physical Education courses once a week (±100 minutes/session), which included fitness exercises, team sports (basketball, soccer, and handball), and basic motor skills training. The training intensity was moderate and did not apply the principle of progressivity. The analysis showed no significant difference between the pre-test VO2max score (83.05) and the post-test score (83.04; p = 0.978). The stability of this value indicates that the physical activity program that lasted for two semesters did not provide sufficient physiological stimulus to increase aerobic capacity. These findings were analyzed using the principles of overload, diminishing returns, and homeostasis, which state that improving fitness requires progressive and intense exercise stimuli. This study recommends applying structured exercise methods, such as HIIT and periodization, to promote more significant physiological adaptations among engineering students.